STAT3 c.1915C > T variant-associated Hyper-IgE syndrome in a child: a case report - Dai, Qianqian; Wang, Yanan; Wang, Zhiyuan; Ru, Liang (Frontiers in Pediatrics, 2025)
BackgroundHyper-IgE syndrome (HIES) is a rare primary immunodeficiency disorder characterized by severe eczema, recurrent skin and respiratory infections, and markedly elevated serum IgE levels. Early diagnosis and management are crucial for prognosis, but clinical misdiagnosis is common due to its rarity. We report a case of a 6-year-old girl with HIES, where a rarely reported STAT3 mutation was discovered through genetic testing, aiming to enhance disease awareness and diagnostic accuracy.MethodsThe patient underwent comprehensive history taking, physical examination, serum IgE measurement, and ancillary tests. Whole-exome sequencing via next-generation sequencing (NGS) was used to analyze the STAT3 gene, with mutation validation by Sanger sequencing. Novelty was assessed against the Genome Aggregation Database (gnomAD). Management included anti-infective therapy, skin care, nutritional support, and a long-term home care plan.ResultsThe child presented with a 5-year history of eczema and skin pustules, growth delay, and malnutrition, along with significantly elevated serum IgE. Genetic testing revealed a heterozygous c.1915C > T missense mutation in STAT3, which was unreported in gnomAD and consistent with HIES pathogenicity based on literature. Supportive care, including anti-infectives and skin management, led to substantial improvement, and long-term home care was implemented post-discharge.ConclusionThe STAT3 c.1915C > T mutation is likely causative of HIES, expanding its genetic mutation spectrum. This case highlights the critical role of genetic testing in rare disease diagnosis and the importance of integrating acute treatment with long-term home care, providing insights for improved early detection and management of HIES.